Pembelajaran Servis Panjang Dalam Permainan Bulu Tangkis Melalui Modifikasi Raket Kayu (Department of Physical Education, Sport, Health and Recreation, 2015)
This research was aims to describe the application of long service learning in the game of badminton rackets using modification of wood because it is perceived very appropriate to increase student studying result, remember advantages of this modification tool is an of the student is able to understand according to the actual object and can develop students' motivation high. The research subjects are students the 6th-grade class student of Sigentong elementary school, amounting to 29 students. This research method is Classroom Action Research (CAR) with two cycles. Result of the research show long service learning in the game of badminton rackets using a modification of wood for the 6th grade Class Student of Sigentong Elementary School in Warureja District Tegal Regency in the Academic Year 2013/2014 from 29 show an increase from the first cycle to the second cycle. Results of first cycle research show the percentage of students achieving 69%.The results of the second cycle of research, an increase in study’s result of 21% of the first cycle, it is 90%. From the results of this research with CAR method can be concluded that the long service learning using wood rackets successfully to increase the ability of long service learning in the game of badminton.